17O-labeled water distribution in the human inner ear: Insights into lymphatic dynamics and vestibular function - Yoshida, Tadao; Naganawa, Shinji; Kobayashi, Masumi; Sugimoto, Satofumi; Katayama, Naomi; Nakashima, Tsutomu; Kato, Yutaka; Ichikawa, Kazushige; Yamaguchi, Hiroshi; Nishida, Kazuki; Sone, Michihiko (Frontiers in Neurology, 2022)
We evaluated the inner ear distribution of 17O-labeled saline administered to the human tympanic cavity. Magnetic resonance imaging was performed after intratympanic administration in five healthy volunteers and one patient with cochlear endolymphatic hydrops. In all volunteers, 17O-labeled water permeated the cochlear basal turn and vestibule at 30 min and disappeared gradually within 2–4 h. All participants experienced positional vertigo lasting a few hours to a few days. Visualization of 17O-labeled water distribution in the endolymphatic space of the posterior ampulla showed indistinct separation of endolymph and perilymph in the cochlea and most of the vestibule in all participants. Intralabyrinthine distribution of 17O-labeled water differed from that in previous reports of intratympanically administered gadolinium-based contrast agent. 17O-labeled water in the endolymphatic space may cause heavier endolymph and positional vertigo. These results of this study may add new insights for investigating the distribution and the effects of molecules in the inner ear after the intratympanic administration in living humans.